Downward wage rigidities in the Mexican labor market 1996-2011 - Laura Juarez; Daniel Casarín de la Cabada (Banco de México, 2016)
In this paper, we provide evidence on the existence and evolution of downward real and nominal wage rigidities in Mexico in the period 1996-2011, which was characterized by a reduction in the level and volatility of inflation. Our results suggest that, throughout the period, a larger fraction of private sector workers, who stayed in the same job from one year to another, were subject to downward real wage rigidities than to downward nominal wage rigidities. The relative importance of downward nominal wage rigidities seems to have increased slightly as inflation decreased, as found in studies for some other countries that achieved a lower and more stable inflation.
Keywords: J30; 330; downward wage rigidities; wage indexation